Clinical Features and MicroRNA Expression Patterns Between AML Patients With DNMT3A R882 and Frameshift Mutations - Yang, Li; Shen, Ke'Feng; Zhang, Mei'Lan; Zhang, Wei; Cai, Hao'Dong; Lin, Li'Man; Long, Xiao'Lu; Xing, Shu'Gang; Tang, Yang; Xiong, Jie; Wang, Jia'Chen; Li, Deng'Ju; et al. (Frontiers in Oncology, 2019)
Background DNA methyltransferase 3A (DNMT3A) plays a unique role in hematopoiesis and acute myeloid leukemia (AML) pathogenesis. While the influences of DNMT3A mutation subtypes are still under debate. Purpose Exploration of the clinical and molecular differences between AML patients carrying DNMT3A R882 mutations and DNMT3A frameshift mutations. Methods Next generation of sequencing (NGS) and clinical data of 118 AML patients in our center were analyzed and compared. NGS, mRNA and miRNA profiling and clinical data from 12 patients in TCGA database were integrative analyzed. Results Among all patients enrolled, 113 patients were positive for the variants of interest. Overall, a total of 295 variants were discovered, among which 24 DNMT3A mutations were detected, including 1 nonsense, 20 missense, 3 frameshift mutations. And 7 DNMT3A R882 mutations (3 R882H, 2 R882C, and 2 R882P) were found. Clinical analysis from our cohort and TCGA database indicated that patients carrying DNMT3A R882 mutation exhibited significantly higher levels of peripheral blood hemoglobin and non-significantly inferior prognosis compared with patients with DNMT3A frameshift mutations. Integrative analysis indicated that miR-10b, miR-143 and miR-30a were significantly decreased in the DNMT3A R882 group. High miR-143 expression is significantly associated with better prognosis in AML patients with DNMT3A mutations. Conclusion Different molecular and clinical characteristics existed between patients with DNMT3A variant subtypes. The distinct microRNA expression pattern for DNMT3A R882 AML patients might not only act as markers to predict disease prognosis, but also could be further investigated to develop novel therapeutic targets for patients with DNMT3A mutations.